SCIENTIFIC AND METHODOLOGICAL CLASSIFICATION OF TRANSLATION METHODS IN LITERATURE - Kamola Aripova Yusupova (Bright Mind Publishing, 2026)
This research paper explores the fundamental essence of translation activity, specifically focusing on the intricate complexities of literary translation. It examines various methodological approaches—ranging from literal (word-for-word) translation to creative, free, and adaptive methods. By analyzing excerpts from Abdulhamid Cho‘lpon’s seminal Uzbek novel Night and Day (Kecha va Kunduz) and its English translation by Christopher Fort, the study highlights the challenges of preserving stylistic nuances, cultural connotations, and the author’s original intent. The article concludes that successful literary translation requires not only linguistic fluency but also deep cultural insight and creative mastery to ensure the target text achieves the same aesthetic impact as the original.
Keywords: Literary translation, Creative translation, Literal translation, Adaptation, Transcreation (Tabdil), Stylistic devices, Cultural equivalence, Night and Day, Peter Newmark, Linguistic gaps, Translation theory.